La posesión efectiva y sus efectos en la partición hereditaria realizada ante el notario - Ayala Quishpe, Majury Raquel (2025)
The effective possession represents a fundamental basis in the Ecuadorian inheritance law, being the act with which it is legally acquired the condition of heir over the assets of the deceased to subsequently allow its partition. The research observes the legal and patrimonial effects of the effective possession in the hereditary partition made before the notary, highlighting its importance in guaranteeing the legal security, protecting the equity in the distribution of the patrimony and preventing conflicts among heirs. The general objective was to identify the effects of effective possession in the hereditary partition carried out before the notary. A qualitative methodology of a descriptive and explanatory type was used, based on documentary and legal analysis, accompanied by semi-structured interviews with notaries with long experience. The main results reveal that effective possession is the key to demonstrate the quality of the heir and his or her inheritance quota, ensuring a fair and transparent partition. However, there are disagreements as to whether a prior inventory is needed, with different opinions as to whether it is useful or not to avoid conflicts and its nonmandatory nature according to the regulations. In addition, the importance of mutual assistance between registries and legislative innovation for agile processes, reducing costs and strengthening legal certainty, to promote agreements between heirs and reduce inheritance conflicts, is distinguished. In conclusion, effective possession not only authenticates the transfer of assets, but also guarantees legal certainty and contributes to a fair and efficient distribution of inheritance.